2018
DOI: 10.1159/000488591
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Exploration on the Effect of the Management of Chronic Obstructive Pulmonary Disease in Rural Areas through an Internet-Based Network Consulting Room

Abstract: Objective: This study aims to improve the management quality of chronic obstructive pulmonary disease (COPD) in rural areas. Methods: Two hundred forty discharged COPD patients were divided into an intervention group and a control group. In the intervention group, 120 patients established contact with doctors through the network consulting room, i.e., the doctor’s mobile platform, and were managed through video, voice, and text by the doctors, kept close contact with the doctors after discharge (education, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…A total of 32 studies met all of the eligibility criteria and were included in this meta‐analysis (Bernocchi et al, 2018; Cameron‐Tucker et al, 2016; Chatwin et al, 2016; Chen et al, 2014, 2021; Demeyer et al, 2017; Jehn et al, 2013; Jiménez‐Reguera et al, 2020; Kessler et al, 2018; Lahham et al, 2020; Li et al, 2014, 2018; Ma, 2019; McDowell et al, 2015; Mínguez Clemente et al, 2020; Park et al, 2020; Pinnock et al, 2013; Rixon et al, 2017; Steele et al, 2008; Tsai et al, 2017; Tupper et al, 2018; Vasilopoulou et al, 2017; Vianello et al, 2016; Vorrink et al, 2016; Walker et al, 2018; Wang et al, 2017; Wang, Guo, et al, 2021; Wang, Di, et al, 2021; Xing et al, 2021; Yan et al, 2018; Ye et al, 2019; Zhang et al, 2020). A flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 32 studies met all of the eligibility criteria and were included in this meta‐analysis (Bernocchi et al, 2018; Cameron‐Tucker et al, 2016; Chatwin et al, 2016; Chen et al, 2014, 2021; Demeyer et al, 2017; Jehn et al, 2013; Jiménez‐Reguera et al, 2020; Kessler et al, 2018; Lahham et al, 2020; Li et al, 2014, 2018; Ma, 2019; McDowell et al, 2015; Mínguez Clemente et al, 2020; Park et al, 2020; Pinnock et al, 2013; Rixon et al, 2017; Steele et al, 2008; Tsai et al, 2017; Tupper et al, 2018; Vasilopoulou et al, 2017; Vianello et al, 2016; Vorrink et al, 2016; Walker et al, 2018; Wang et al, 2017; Wang, Guo, et al, 2021; Wang, Di, et al, 2021; Xing et al, 2021; Yan et al, 2018; Ye et al, 2019; Zhang et al, 2020). A flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…All relevant data were documented in the electronic health records to allow the administrators and patients to refer to relevant information using the internet (Wang et al, 2017). In 15 studies, patients in the intervention groups received multicomponent telehealth, including telerehabilitation, telemonitoring, and self‐management programmes (Chen et al, 2014, 2021; Demeyer et al, 2017; Jiménez‐Reguera et al, 2020; Kessler et al, 2018; Lahham et al, 2020; Ma, 2019; Park et al, 2020; Vorrink et al, 2016; Wang, Di, et al, 2021; Wang, Guo, et al, 2021; Xing et al, 2021; Yan et al, 2018; Ye et al, 2019; Zhang et al, 2020). The duration of home‐based telehealth interventions ranged from 8 weeks to 24 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings confirmed that the use of the network consulting room (e.g. mobile platform, with patient interacting through video, voice and text with the doctors) can improve the quality of life of patients and reduce the number of re-hospitalization [ 46 ]. A recent literature review suggested that web-based interventions, for supporting informal caregivers of adult people with chronic conditions living in the community, can improve general health outcomes of caregivers themselves (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…It enables services such as outpatient appointments, refilling medications, making payments and downloading medical history. These services effectively improve patients' medical experience and contribute to the improvement of their quality of life (Yan et al, 2018;Yang et al, 2019). On the contrary, patients with COPD are prone to anxiety, depression and other psychological problems when facing symptoms such as dyspnoea due to the long duration of the disease and recurrent episodes (Lou et al, 2012).…”
Section: Summaryandinterpretationoffindingsmentioning
confidence: 99%